微生物岩土技术的研究进展 = Research advances in biogeotechnologies - 何 稼 He, Jia (2016)
岩土体中存在着大量的微生物，这些微生物的活动对岩土体的物理、力学性质有一定的影响。微生物岩土技术，是将微生物反应加以控制和利用，来解决岩土工程中的问题。在近十年里，微生物岩土技术逐渐成为岩土工程研究界的一个热门课题，并取得了很大的进展。从原理和应用两个角度对这一领域的研究进行归类和分析。从微生物反应原理的角度来说，微生物岩土技术所利用的微生物过程包括微生物矿化作用，微生物产气泡过程，以及微生物膜生长过程等。从实际应用的角度来说，微生物岩土技术的应用领域包括岩土体加固、防渗，砂土液化防治，土体抗侵蚀，污染土治理等。此外，还对微生物岩土技术的实施方法特点，监测和检测技术，以及环境影响进行了介绍。There is a large number of microorganisms in soil and rock masses. The activities of these microorganisms can influence the physical and mechanical behaviours of soils and rocks. These microbial activities can be controlled, enhanced, and used to solve geotechnical problems. Such methods have been named as biogeotechnologies. In the last decade, the biogeotechnologies have received increasing research efforts and gained great advances. This study aims at classifying and evaluating these studies from two aspects, mechanisms and applications. From the aspect of mechanisms, microbial processes that can be adopted by the biogeotechnologies include biomineralization, biogas generation, and biofilm growth, etc. From the aspect of applications, the biogeotechnologies can be used for the strengthening of soils and rocks, sealing of water leakage, prevention or mitigation of soil liquefaction, soil erosion control, and rehabilitation of contaminated soils, etc. In addition, the construction methods, monitoring and quality inspection techniques, and environmental impacts of biogeotechnologies are also introduced.